Presentation, The Best Model for Teaching Speaking for Adults Students - Budiyanto, S M.; Haryanto, Sigit (Jurnal VARIDIKA, 2019)
The aim of the research is to show that presentation is one of the best models for teaching speaking for Adult students. This research and development study consists of exploration, designing model draft, validating model, experts jugment, revising model, implementing model, data description, data analysis, findings and discussion, recommendation, revising, the final model and dissemination. Technique of data collection was obtained by using test, interview, and observation; Technique of data analyze for quantitative data used non independent t-test. The researcher also used descriptive statistic including highest, average, and lowest scores. To analyze the qualitative data, the researcher used trianggulation and flow model of analysis. The research results showed that The first model results showed that: it improved the students’ bravery to speak up in front of the audience and made a better condition of the students’ speaking environment. The second model results showed that the development of the students’ speaking ability growing up rapidly and their grammar and vocabulary also getting better. The Final Model results showed that there is very clear improvement on their bravery to speak up infront of the audience. Their learning progress and speaking ability grew up rapidly, theirgrammar and vocabulary also increased significantly. The computation result showed thatall of the results is higher than tt (2,02). It showed that Developing a model of teachingspeaking through presentationis good, suitable and accurate for teaching and improvingthe Students’ Speaking Ability of accounting education of UMS is proved correct andsignificant.